New stoichiometric compounds of Au–Hg system under high pressure. (22nd May 2019) - Aslam, Muhammad Aamir; Ding, Z J
Abstract: We have extensively explored Au–Hg system under high pressure in the range of 0–300 GPa with and without spin–orbit coupling (SOC) inclusion. The variable-composition methodology has been used as employed in Universal Structure Predictor: Evolutionary Xtallograpgy (USPEX) in combination with Vienna Ab initio Simulation Package (VASP). We have predicted several thermodynamically stable stoichiometric compounds of Au–Hg system, i.e. Au3 Hg (space group 194, P63/mmc ), AuHg (space group 62, Pnma ), AuHg2 (space group 15, C2/c ), AuHg9 (space group 38, Amm2 ) at 50 GPa; AuHg3 (space group 44, Imm2 ) at 100 GPa; Au3 Hg2 (space group 15, C2/c ) at 200 GPa and AuHg4 (space group 15, C2/c ) at 300 GPa. We also found a phase transition of AuHg3 from Imm2 to P63/mmc at 248.5 GPa and 246.5 GPa with and without SOC, respectively.